Utilization Of Exhaust Air Conditioning In Apartments For Hot Water Supply: Overview Of Economic Aspects - Andreas, Andreas (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2022)
The economic crisis that has hit almost all parts of the world has forced everyone to rethink their own economic arrangements. One thing to consider is the use of hot water. Not by eliminating it, but by looking for other alternatives to produce hot water. The heat-generating system that is widely used by the community is the electric water heater. On the one hand, this system works effectively because it can produce hot water with a maximum temperature of 750C. But on the other hand this system is not economical, because the electricity costs are very large. An alternative that can be given is the use of Air Conditioning Water Heater. Compared to the use of other types of water heaters, hot water produced by ACWH can be said to be "free hot water" because it is produced by utilizing the exhaust heat of the air conditioner and does not require additional electricity costs. The purpose of this research is to determine the most economical type of water heater. The research includes variations in the price of water heaters on the market and the electricity costs paid. From the results of the research, it was found that the most economical type of water heater is ACWH PK with an accumulated electricity cost of Rp. 5.010.300,- in the first year to Rp. 15.003.008,- in the 10th year. The results of this study are expected to be a solution to the economic crisis that hit almost the whole world. In addition, the ACWH system is also environmentally friendly and can reduce global warming because it does not consume energy and utilizes waste heat as its energy source.